Protocol to Retrieve Unknown Flanking DNA Using Fork PCR for Genome Walking - Hongjing Wu; Hao Pan; Haixing Li (Bio-Protocol)
PCR-based genome walking is one of the prevalent techniques implemented to acquire unknown flanking genomic DNAs. The worth of genome walking includes but is not limited to cloning full-length genes, mining new genes, and discovering regulatory regions of genes. Therefore, this technique has advanced molecular biology and related fields. However, the PCR amplification specificity of this technique needs to be further improved. Here, a practical protocol based on fork PCR is proposed for genome walking. This PCR uses a fork primer set of three arbitrary primers to execute walking amplification task, where the primary fork primer mediates walking by partially annealing to an unknown flank, and the fork-like structure formed between the three primers participates in inhibiting non-target amplification. In primary fork PCR, the low-annealing temperature (25 °C) cycle allows the primary fork primer to anneal to many sites of the genome, synthesizing a cluster of single-stranded DNAs; the subsequent 65 °C cycle processes the target single-strand into double-strand via the site-specific primer; then, the remaining 65 °C cycles selectively enrich this target DNA. However, any non-target single-stranded DNA formed in the 25 °C cycle cannot be further processed in the following 65 °C cycles because it lacks an exact binding site for any primer. Secondary, or even tertiary nested fork PCR further selectively enriches the target DNA. The practicability of fork PCR was validated by walking three genes in Levilactobacillus brevis CD0817 and one gene in Oryza sativa. The results indicated that the proposed protocol can serve as a supplement to the existing genome walking protocols.